2003
DOI: 10.1016/j.mrfmmm.2003.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Repair of and checkpoint response to topoisomerase I-mediated DNA damage

Abstract: Topoisomerase I (Top1) catalyzes two transesterification reactions: single-strand DNA cleavage and religation that are normally coupled for the relaxation of DNA supercoiling in transcribing and replicating chromatin. A variety of endogenous DNA modifications, potent anticancer drugs and carcinogens uncouple these two reactions, resulting in the accumulation of Top1 cleavage complexes. Top1 cleavage complexes damage DNA and kill cells by generating replication-mediated DNA double-strand breaks (DSBs) and by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
243
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(250 citation statements)
references
References 252 publications
(341 reference statements)
2
243
0
5
Order By: Relevance
“…Understanding the transcriptional response to Top1cc is of particular interest as the CPT derivatives irinotecan and topotecan are used to treat human cancers. 18 Moreover, transcriptional responses to Top1cc may occur spontaneously under normal conditions as Top1cc are readily stabilized by endogenous DNA alterations, 15,52,53 which may lead, if not repaired, to neurological diseases such as SCAN1. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Understanding the transcriptional response to Top1cc is of particular interest as the CPT derivatives irinotecan and topotecan are used to treat human cancers. 18 Moreover, transcriptional responses to Top1cc may occur spontaneously under normal conditions as Top1cc are readily stabilized by endogenous DNA alterations, 15,52,53 which may lead, if not repaired, to neurological diseases such as SCAN1. 54 …”
Section: Discussionmentioning
confidence: 99%
“…In this case, a trapped DNA:topoisomerase 1 (Top1) complex comprises the lesion. Top1 is essential for the relaxation of DNA supercoiling ahead of the replication machinery [53,54]. If Top1 is inhibited either chemically (for example through the action of the chemotherapeutic drug camptothecin) or as a result of clustered ROS damage, the protein remains bound to the DNA creating a toxic single-strand break in actively replicating cells [55].…”
Section: Strand-breaks Generated By Topoisomerase Poisonsmentioning
confidence: 99%
“…After lesion removal by Tdp1, PNKP can then transfer the phosphate group from the 3' to the 5' terminus, thus preparing the DNA ends for repair [58]. If any gapfilling activity is required, pol ß is considered a likely candidate [54,[59][60][61][62]. Interestingly, both PNKP and pol ß are known to interact with XRCC1 and it has recently been reported that Tdp1, critical for the repair of these Top1-mediated lesions, co-immunoprecipitated with XRCC1 [61].…”
Section: Strand-breaks Generated By Topoisomerase Poisonsmentioning
confidence: 99%
“…However, a variety of conditions (briefly schematized in Fig. 1B), have been shown to increase the frequency of Top1-DNA cleavage complexes by reducing or inhibiting the rate of the religation reaction (for reviews see [7,8]). For example, Top1 inhibitors, such as camptothecin (CPT) and its clinically used derivatives, as well as several non-CPT Top1 inhibitors including the indenoisoquinolines and the indolocarbazoles, selectively and reversibly bind to the Top1-DNA interface [6,9] and slow the rate of Top1-mediated DNA religation.…”
Section: The Formation Of Irreversible Top1 Cleavage Complexesmentioning
confidence: 99%